AB0227 Biologic therapy does not increase infection risk scores in a diverse ethnic minority rheumatoid arthritis cohort (emrac). (23rd January 2014) - Kerr, G.; Yazici, Y.; Swearingen, C.; Luo, C.; Espinoza, L.; Sherrer, Y.; Treadwell, E.; Mosley-Williams, A.; Alamino Perez, R.; Bata, Y.; Dowell, S.; Godoy, A.; et al.
Abstract : Background: Comorbities, advanced age, and prednisone usage are known risk factors for infection in RA patients who already have compromised immune systems. However, both the infection risk in ethnic minorities with RA and the utility of biologic use as a predictor are unknown. Objectives: To evaluate infection risk scores (IRS) 1 in a diverse ethnic minority RA cohort, and the effect of biologic therapy. Methods: Enrolled, consented EMRAC patients were evaluated. IRS measures including socio-demographic (age), previous patient-reported serious infections, extra-articular RA (amyloidosis, Felty's syndrome, vasculitis, pleuritis), RA disease activity-parameters (ESR), prednisone usage, comorbidities (HTN, DM, lipidemia, CVD event), and biologic were abstracted. IRS were estimated using (1) as-published methods, (2) substituting current biologic use for inferred infection risk, and (3) adding current biologic use to published method. Comparisons of IRS risk categories as well as other categorical data was analyzed between ethnic groups using Chi-square test; differences in continuous measures between ethnic groups were estimated using Kruskal-Wallis test. Results: 468 EMRAC subjects were available for analysis: 393 were female (84%) with mean age of 56.4 years; 183 were Caucasian (39%), 169 were African American (AA) (36%), 79 were Hispanic (17%), and 37 were Other (8%). Comorbidities were reported in 19%, biologic therapy use in 32%, and previous infections in 3%. With previously reported infection, estimated IRS was significantly higher in AAs compared to other ethnic subsets (16% had a 5-10% risk compared to 5%, p=0.001), but was not significant when biologic use was included, either with or without previous infection. Conclusions: Compared to Caucasians/other ethnic subsets, African American RA patients with previous infections are at increased risk for recurrence. These data suggest a need for increased surveillance for recurrent infections in African American RA patients, and a potential impact on treatment decisions. References: Crowson, C. Arth. Rheum, 2012. Acknowledgements: Genentech, Pfizer, Bristol Myers Squibb Disclosure of Interest: G. Kerr Grant/research support from: EMRAC Group receives unrestricted grant support from Genentech, Pfizer and Bristol Myers Squibb, Y. Yazici: None Declared, C. Swearingen: None Declared, C. Luo: None Declared, L. Espinoza: None Declared, Y. Sherrer: None Declared, E. Treadwell: None Declared, A. Mosley-Williams: None Declared, R. Alamino Perez: None Declared, S. Dowell: None Declared, A. Godoy: None Declared, M. Paul: None Declared